« first day (479 days earlier)      last day (2633 days later) » 

13:00
Doesn't make sense why you have 3 zeros and 1 one.
That's why I was saying it must be wrong.
> Let G be the following program on input (P,X):
For each string s in length-lexicographic order:
If V( "The program P halts on input X and outputs 0." , s ) then output 0.
If V( "It is not true that the program P halts on input X and outputs 0." , s ) then output 1.
funny
Oh lol.
your write-up has exactly 3 zeros and 1 one
Argh my intuition is failing badly.
are you alright
sleep deprivation?
not awake?
13:01
I'm alright but a bit too lazy today.
move on
But we can't move on anyway; this is the crucial part; we don't have an obvious way to prove that G exists.
then how should I translate that part?
Well the way I would do it is to simply translate the entire program as one piece. Rather than to try following a Godel-proof-like approach.
Namely, you see the definition of G in my post, right?
It's a well-defined program.
which corresponds to a formula
13:05
Just dump it into the system as a formula, and then apply the unsolvability proof.
Yea.
but I want to write the formula
But I think you won't be too satisfied with that.
@user21820 you know me too well
Well it's not hard, is it? It's a program so there is a 2-parameter sentence that corresponds to it.
3-parameter, since I have two inputs
> it's not hard, is it?
we're doing this again
13:07
That's also fine; I had in mind combining (p,x).
13 mins ago, by Leaky Nun
I'm saying, instead of telling me repeatedly that I'm wrong, which I know I am, just translate it to PA correctly
I already did it once
you said it's wrong
and your comment now is "it's not hard, is it?"
no it isn't, but I don't know how to do it
But you do; γ(p,x,y) ≡ ( p(x)=0 ∧ y=0 ∨ p(x)≠0 ∧ y=1 ).
Pass it through the encoding.
And you'll get a γ that represents G.
γ(p,x,y) ≡ ( p(x,0) ∧ y=0 ∨ p(x,n) ∧ n≠0 ∧ y=1 )
With an existential.
in the front?
13:11
γ(p,x,y) ≡ ( p(x,0) ∧ y=0 ∨ ∃n ( p(x,n) ∧ n≠0 ) ∧ y=1 )
are they equivalent?
anyway
The two I wrote are equivalent at the high-level. After encoding, they remain equivalent because the system is assumed consistent and Σ1-complete.
It can prove every true Σ1-sentence, which is the same as saying can reason about programs.
wait, you dropped the Bew
Oh.
Forgot.
Could you write G though
G(P,x,n) := Bew("Q(x,0)") ∧ y=0 ∨ ∃m (m≠0 ∧ Bew("Q(x,m)")) ∧ y=1)
13:16
No that's not correct, because we must have the negation under the box.
γ(p,x,y) ≡ ( ⬜p(x,0) ∧ y=0 ∨ ⬜¬p(x,0) ∧ y=1 )
oh right
why do you keep using gamma?
G(P,x,n) := Bew("Q(x,0)") ∧ y=0 ∨ Bew("¬Q(x,0)") ∧ y=1)
To emphasize that it's not the same as the program G.
But never mind.
To prove: for all P and X, ⊢[G(P,X,0)⟺Q(X,0)], where P="Q".
Assume ⊢Q(X,0) outside the system
Then, ⊢Bew("Q(x,0)")
can't prove it inside the system...
Right. This must be meta.
then how do I prove that property?
13:19
Oh your zero-guessing problem was too strong.
> If P halts on X, then the answer is 0 if P(X) = 0 and is 1 otherwise. (If P does not halt on X, then any answer is fine.)
but then I would need soundness
No you don't, you can say "if P halts on X".
what does that mean in PA-?
Halting is just a Σ1-sentence.
Wait copy your attempt:
> Let G be a formula such that for all P and X, ⊢[G(P,X,0)⟺Q(X,0)], where P="Q".
Correct should be:
> Given G be a 3-parameter sentence over S such that for any program represented by a 2-parameter sentence P coded by p such that ( N |= P(x,k) for some natural k ), we have S |− G(p,x,0) ⇔ P(x,0), ...
I think.
That's why I hate doing it this way; so prone to error.
that's why I love doing it that way :P
13:34
Then your D looks wrong now too...
I'm getting a headache doing it this way.
The reason is that instead of using programs you are trying to use formulae, but that's very troublesome because you can't just use any formulae but those that represent programs..
So it gets messy quick.
If you want to go the formula way, I think all you need is a stronger fixed-point theorem.
The usual one says that given any 1-propositional-parameter sentence F whose parameter is under the ⬜, you can construct a sentence P such that the system can prove P⇔F(P).
That's like recursion with 1 program.
You need recursion with 2 programs.
I think.
Namely given any 2-propositional-parameter sentences F,G whose parameters are under the ⬜, you can construct sentences P,Q such that the system can prove P⇔F(P,Q) and Q⇔G(Q,P).
what do I get if I use “not X” as my formula for my usual fixed point theorem?
13:42
You can't; the parameter must be under the ⬜.
If you look again at the proof of the fixed-point theorem you will see that you can only construct the sentence when only its code is used recursively, not its truth value.
So as long as it is under the box it is fine.
But let me do something else for today. Not really in the mood for playing with 2d-modal-fixed-point theorems.
 
3 hours later…
17:01
@KennyLau What would convince me is a proof that a proof for this question requires induction; just saying it's necessary will not. — Duncan Ramage 1 hour ago
@user21820 lol
 
6 hours later…
23:25
@user21820 how is this?

« first day (479 days earlier)      last day (2633 days later) »